Perlindungan Konsumen dalam Industri Halal: Tinjauan UU No. 8 Tahun 1999 dari Perspektif Hukum Islam - Wahab, Fatkhul; Ihsan, Moh. (Program Studi Perbankan Syariah STAI Senori Tuban, 2024)
Consumer protection in the halal industry is an increasingly important issue as the sector grows in the global market. This article discusses the challenges faced in the implementation of consumer protection regulations, particularly concerning compliance with halal standards. Despite the existence of the Consumer Protection Law (UUPK), many industry players have not fully complied with its provisions, to the detriment of consumers. From the perspective of Islamic law, consumer protection is not only concerned with legal aspects but also with business ethics and morality, where the principles of fairness, responsibility, and transparency are important cornerstones. This article also highlights the role of the government and relevant agencies in ensuring compliance with halal standards and the protection of consumer rights. Through this study, it is hoped that a comprehensive solution can be found to improve consumer protection in the halal industry, by the principles of Islamic law. This study recommends increased supervision, law enforcement, and education to the public to strengthen the position of consumers against business actors.